2009
DOI: 10.1016/s1130-1473(09)70177-0
|View full text |Cite
|
Sign up to set email alerts
|

Características morfológicas de aneurimas cerebrales del polígono de Willis: estudio anatómico directo

Abstract: The aneurysm prevalence in the evaluated sample was similar to the reported in other populations. In this work, the presence of aneurysms on the origin of the anterior chorioid artery, an unusually reported localization, was prominent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…This portion of the circle of Willis is the preferable area for aneurysm formation. The aneurysm of the ACoA presents about 30% of all cerebral aneurysms [7, 18]. Surgical procedures such as applying temporary clips in the anterior part of the circle of Willis or small excision of the gyrus rectus may cause damage or occlusion of the RAH.…”
Section: Discussionmentioning
confidence: 99%
“…This portion of the circle of Willis is the preferable area for aneurysm formation. The aneurysm of the ACoA presents about 30% of all cerebral aneurysms [7, 18]. Surgical procedures such as applying temporary clips in the anterior part of the circle of Willis or small excision of the gyrus rectus may cause damage or occlusion of the RAH.…”
Section: Discussionmentioning
confidence: 99%
“…All this evidence may relate to more fragile wall disposition as it is not fully matured, or to altered hemodynamics secondary to the anatomical variation. A cadaveric study of the mestizo population in Colombia showed that aneurysm prevalence was associated to asymmetric configuration of the circle of Willis 104 . The most common variation was hypoplasia of the PCOM, which highlights the importance of the effects of hemodynamic dominance.…”
Section: Locationmentioning
confidence: 99%
“…Firstly, it is faster and requires no additional fixation of brain tissue or vessels, thus simplifying the process and saving materials. This can be evinced when compared to other studies such as those undertaken by other investigators [1][2][3][4][5][6][7][8][9][10][11][12]. It also reduces the need for complimentary studies during the autopsy.…”
Section: Discussionmentioning
confidence: 95%
“…Vinylpolisiloxane silicone had not been used before in forensic studies. It offers some advantages in comparison to other materials used in previously published literature: self-curing silicones [1,2], elastomers [3], colored-latex [4,5], polyurethane [6] or different procedures with resins [7,8,9,10], as both economic and rapidity in time, among others. The solidifying time of vinylpolisiloxane is significantly quicker than other mixtures [1,4,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation